Comprehensive computer program for SSTI analysis of AC/DC power systems based on the component connection method. (October 2019) - Dimitrovski, Robert; Mehlmann, Gert; Luther, Matthias; Ndreko, Mario; Winter, Wilhelm; Trunk, Kai; Rachinger, Sarina
Highlights: The advantages of the CCM are combined with a network state equations algorithm. Comprehensive linear MMC model is developed. The methodology can be used prior to the commissioning of new HVDC systems. Abstract: This paper presents a comprehensive methodology for the investigation of SSTI in AC/DC transmission networks. The main advantage of the proposed methodology is the modular modeling approach, where various complex components can be modeled in a comprehensive way while at the same time preserving the level of detail needed to capture the relevant dynamics. This is done by enhancing the CCM with an algorithm for the formulation of network state equations. All power system component models necessary for SSTI analysis are developed separately using the CCM principles and are connected according to their topological relations. A small-signal model of a point-to-point MMC-based VSC HVDC is developed to assess its influence on SSTI. The proposed methodology together with the developed models are implemented in a software framework called SNAP. The proposed methodology and the developed models are validated against time-domain simulations in PSS®NETOMAC.